2020
DOI: 10.18799/24056537/2020/2/262
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Carboxymethyl Cellulose and Partially Hydrolyzed Polyacrylamide – Low-Solid Nondispersed Drilling Mud With Respect to Proper-Ty Enhancement and Shale Inhibition

Abstract: During drilling, different problems are encountered that can interfere with smooth drilling processes, including the accumulation of cuttings, reduced penetration rates, pipe sticking, loss of wellbore stability, and loss of circulation. These problems are generally encountered with conventional drilling mud, such as the bentonite–barite mud system. Formation damage is the most common problem encountered in bentonite mud systems with high solid content. In this work, we aimed to formulate two low-solid nondisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, eco-friendly additives such as starch, polyphenols, and lignosulfonate showed a good filtration performance in Bentonite-water-based drilling fluids [16], along with the use of single-walled carbon nanotubes/polyvinyl pyrolidone (SWCNs/PVP) nanocomposites on the drilling efficiency of water-based muds, with the last forming a protective layer on the shale surface to obstruct the access of water and offering structural stability of the drilling mud [17]. Partially hydrolyzed polyacrylamide (HPAM) is a water-soluble polymer material used in oil fields [18,19]. It usually has a linear structure with high molecular weight [20] and is obtained by partial hydrolysis of PAM or by copolymerization of sodium acrylate with acrylamide [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, eco-friendly additives such as starch, polyphenols, and lignosulfonate showed a good filtration performance in Bentonite-water-based drilling fluids [16], along with the use of single-walled carbon nanotubes/polyvinyl pyrolidone (SWCNs/PVP) nanocomposites on the drilling efficiency of water-based muds, with the last forming a protective layer on the shale surface to obstruct the access of water and offering structural stability of the drilling mud [17]. Partially hydrolyzed polyacrylamide (HPAM) is a water-soluble polymer material used in oil fields [18,19]. It usually has a linear structure with high molecular weight [20] and is obtained by partial hydrolysis of PAM or by copolymerization of sodium acrylate with acrylamide [21].…”
Section: Introductionmentioning
confidence: 99%
“…Kuma KCl and NaCl acted as great swelling inhibitors for drilling muds, while haematite just slightly increased the rheological properties on CMC-bentonite mud and did not have much effect on the PHPA-bentonite mud [26]. Das et al compared CMC and HPAM and it was found that the PHPA mud exhibited a higher effective viscosity, apparent viscosity, and plastic viscosity than the CMC mud; the PHPA also showed higher values of yield point and gel strength which indicated that PHPA mud has a better cutting-carrying capacity than CMC mud [19]. Laura et al compared partially hydrolyzed polyacrylamide and xanthan gum (XG).As it was expected, HPAM solutions and nanopolymer sols were more sensitive to salinity and temperature changes than the XG sols [29].…”
Section: Introductionmentioning
confidence: 99%